Value Education on Pela Tradition (An Ethnographic Study of Ambonese) - Frans Thomas (Pascasarjana UM, 2015)
Pendidikan Nilai dalam Tradisi Pela (Kajian Etnografis Masyarakat Ambon)Abstract: The value that has meaning in pela tradition in Ambon society is something that has been handled as personally and can be internalized in human behaviour. The reality of pela tradition value order has been processing in institutionalized as the education direction of social values. The purpose of this qualitative research is to describe the values in the tradition of pela for educational value in Ambon community. The Exposure to the data, data explanation and understanding of discourse data tradition of pela is done in depth. The Study of pela discourse tradition with hermeneutics gives holistic-emic views of how the tradition of pela is able to package and legitimize the Ambonese community life philosophy. The results of the study describes the values in the tradition of pela include (1) the value of religion that regulates the dimensions of God in human life, (2) the value of the philosophy that is universal and will be impacted by the ending value and subjectivity, and (3) the value of ethical consequences of individual responsibility in achieving a moral obligation. Key Words: value education, culture, pela traditionAbstrak: Nilai yang memiliki arti dalam tradisi pela masyarakat Ambon adalah sesuatu yang telah diberikan sejak turun temurun secara pribadi dan dapat diinternalisasi dalam perilaku manusia. Pada kenyataannya, nilai pada tradisi pela telah dilembagakan menjadi arahan dalam pendidikan nilai-nilai sosial. Tujuan penelitian kualitatif ini adalah menggambarkan nilai-nilai yang terkandung dalam tradisi pela sebagai pendidikan nilai masyarakat Ambon. Paparan data, cara penjelasan data, dan pemahaman data wacana tradisi pela dilakukan secara mendalam. Kajian wacana tradisi pela dengan ancangan hermeneutika memberikan gambaran holistik-emik tentang bagaimana tradisi pela mampu mengemas dan melegitimasi falsafah hidup komunitas masyarakat Ambon. Hasil penelitian memaparkan nilai-nilai dalam tradisi pela meliputi (1) nilai agama yang mengatur dimensi tuhan dalam kehidupan manusia, (2) nilai filosofi yang memiliki universal dan akan terpengaruh berakhir nilai dan subjektif, dan (3) nilai etika yang memiliki konsekuensi tanggung jawab individu dalam mencapai kewajiban moral. Kata kunci: nilai pendidikan, budaya, tradisi pela